2017
DOI: 10.1186/s13052-017-0354-z
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of drug use among preterm neonates: results from an Italian neonatal intensive care unit

Abstract: BackgroundDrug use in preterm neonates admitted to Neonatal Intensive Care Unit (NICU) has been investigated, so far, in terms of unauthorized or off-label use; very little is known on the use of combinations of different active substances, which is frequently required in this population (prophylaxis of infections, treatment of concomitant diseases). The aim of this study was to describe the most common patterns of drug use in an Italian NICU, focusing on those with nephrotoxic potential.MethodsMedical records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…In the present study, antibiotics were the most commonly used off-label medicines compared to the other classes of medicines. This was similar finding with that of study reports from Iran and Italy [3,24]. However, it was different from a study conducted in Netherlands which reported that blood products were the top class of medicines used in an off-label manner [20].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the present study, antibiotics were the most commonly used off-label medicines compared to the other classes of medicines. This was similar finding with that of study reports from Iran and Italy [3,24]. However, it was different from a study conducted in Netherlands which reported that blood products were the top class of medicines used in an off-label manner [20].…”
Section: Discussionsupporting
confidence: 84%
“…The use of off-label and unlicensed medicines was found to differ by the gestational age of the neonates. Many studies elsewhere in the world reported high rate of off-label [11,12,22,24] and unlicensed [11] medicine use among pre-term neonates. Despite the number of post-term neonate were very small in our study, off-label prescriptions were relatively higher for post-term and preterm neonates where (8/8) and (43/45) of the postterm and pre-term neonates were exposed to at least one off-label medicines respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Europe (24 studies) [7,13,20,25,26,29,31,35,37,[42][43][44]50,59,62,63,65,67,68,71,[74][75][76]79] caffeine (18 studies), gentamicin (17 studies), ampicillin (11 studies), furosemide (9 studies), multivitamins (9 studies), vitamin K (11 studies), benzylpenicillin (8 studies), amikacin (6 studies), morphine (5 studies), paracetamol (6 studies)…”
Section: Geographic Region (Number Of Studies) (Ref) Most Frequently mentioning
confidence: 99%
“…Thus, antibiotics are the most frequently prescribed medicines, followed by drugs for respiratory and nervous diseases in neonates, especially if with a gestational age below 32 weeks and/or birth weight < 2500 g. Almost 90% of the drugs used in neonatal intensive care units (NICUs) are off-label or unlicensed [ 101 ] and they are administered intravenously [ 102 ]. Girardi et al have recently evaluated the drug use in neonates with low and extremely low birth weight at an Italian NICU [ 103 ]. They found that, compared to neonates with low birth weight, babies with very low birth weight were exposed to a higher number of drugs, mainly antibiotics, antifungals, and diuretics, and received more frequently associations of potentially nephrotoxic drugs.…”
Section: Reviewmentioning
confidence: 99%